Analysis of Potentials and Chances of Agrotourism Development in Batu - Ahmad Faidlal Rahman (Program Pendidikan Vokasi Universitas Brawijaya, 2013)
Agrotourism needs to be developed continuously in order to give diversification of tourism products. The development is based on the fact that there is a changing motive of tourists from public interest to special one. Batu, as an administrative area, has chances to be developed as a destination of agrotourism because this city has natural beauty, farm and plantation. Regarding this, this article aims to describe potentials and chances of agrotourism development in Batu. The data analysis was done inductively in which the data collection was done to make abstraction instead of hypothesis testing. From the data collection and analysis, it can be concluded that Batu can be considered as a destination of agrotourism which focuses more on product development (product-oriented) instead of market development (market-oriented).